Zusammenbildungen in der deutschen und polnischen Gegenwartssprache - Bzdęga, Andrzej Z. (Wydawnictwo Naukowe UAM, 1984)
The aim of the paper is to give an appropriate structural interpretation of a very productive kind of word-foimation which results from simultaneous composition and derivation processes, and in German word-formation is called “Zusammenbildung”. After some general statements on the importance of word-formation rules in foreign language teaching the author is trying to describe two different types of “Zusammenbildung’' in German and their counterparts in Polish, pointing at several striking correspondences, and some inadequacies in their up to now interpretation.